Argentina : Escaping Crises, Sustaining Growth, Sharing Prosperity - World Bank Group (World Bank, Washington, DC, 2018)
Argentina is rich in natural capital assets and has a historically strong middle class. Nonetheless, compared to that of its peers, Argentina’s long-run economic performance has been disappointing, affecting the country’s ability to reduce poverty and increase incomes of its citizens.This report is an analysis on the medium-term agenda to ensure growth and shared prosperity in Argentina and comes at a time when the country is embarking on deepening structural reforms while dealing with recent sudden financial market pressures that emerged in April 2018. The focus of the report is on medium- to longer-term development challenges in Argentina, rather than contemporaneous macroeconomic developments. The report looks at the policies needed to Argentina to end its vicious circle of fourteen economic crisis since 1950, that the country experienced. This includes a substantial focus on macroeconomic policies to set in place the foundations for medium-term growth and shared prosperity by boosting jobs and productivity.